Confirmation of the presence of Chorthippus apricarius (Linnaeus, 1758) (Caelifera, Gomphocerinae) in Slovenia - Paul Veenvliet (Natura Sloveniae)
In summer 2004, Chorthippus apricarius was found on Bloke plateau. This finding confirms the presence of this species in Slovenia, which was previously only documented in two unpublished camp reports.